2010
DOI: 10.1159/000317252
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 30-Day Mortality between Anterior-Wall versus Inferior-Wall ST-Segment Elevation Myocardial Infarction Complicated by Cardiogenic Shock in Patients Undergoing Primary Coronary Angioplasty

Abstract: Objectives: In this study, 30-day mortality from cardiogenic shock caused by left anterior descending artery (LAD) occlusion was compared with that caused by left circumflex (LCX) or right coronary artery (RCA) occlusion after primary percutaneous coronary intervention (PCI). Methods: Between May 2001 and December 2009, 212 consecutive patients with anterior-wall ST-elevation myocardial infarction complicated by cardiogenic shock due to LAD (n = 97) occlusion (group 1) and LCX or RCA (n = 115) occlusion (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The highest inhospital mortality was observed in the left main (64.7%) and the lowest in the RCA group (30.8%) [17]. In the study by Zeymer [7]. An association between unsuccessful reperfusion and favorable clinical outcomes has been confirmed in previous studies [3,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The highest inhospital mortality was observed in the left main (64.7%) and the lowest in the RCA group (30.8%) [17]. In the study by Zeymer [7]. An association between unsuccessful reperfusion and favorable clinical outcomes has been confirmed in previous studies [3,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 68%
“…Relatively limited data are available assessing the relationship between the infarct-related artery (IRA) and the in-hospital and long-term outcomes of patients with MI complicated by CS [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to earlier studies, our large-scale registry showed that 7.1% patients underwent primary PCI presented with cardiogenic shock and, of these, 374 patients (56.6%) had MVD. These findings suggest that recent therapeutic improvements such as early revascularization strategy, inotropic agents, vasoconstrictors, adjunctive medications, and assist devices might contribute to improve survival, although in-hospital mortality of cardiogenic shock remains still high (16,17,23,24). There are several possible explanations for relatively low mortality in our study.…”
Section: Cardiogenic Shock In Real-world Practicementioning
confidence: 64%
“…For patients undergoing primary PCI for STEMI complicated by cardiogenic shock, recent studies showed an in-hospital mortality of 30-40% (16)(17)(18). MVD is noted in 40-65% of patients undergoing primary PCI for STEMI and is associated with adverse prognosis (8,19,20).…”
Section: Cardiogenic Shock In Real-world Practicementioning
confidence: 99%
“…Furthermore, as acknowledged by the authors, rightventricular function was not assessed, therefore we do not know how many patients from the 'inferior' group in shock actually had predominant, or even significant, involvement of the right ventricle. Needless to say, these patients have a completely different pathophysiology and In this issue of Cardiology , Tsai et al [1] report on a large series of patients with cardiogenic shock due to AMI of ! 12 h duration, all treated with primary PCI, recruited over a period of 7 years.…”
mentioning
confidence: 99%